First report of two Mesocriconema (Nematoda: Criconematidae) species in mulberry trees in Costa Rica - Walter Peraza-Padilla (Pesquisa Agropecuária Tropical, 2014)
Soil samples were collected from the rhizosphere of mulberry (Morus alba L.) trees, in a 1,000 m2 plot, at the Experimental Farm Santa Lucia, in Barva, Heredia, Costa Rica, in August 2013. The plants showed symptoms of yellowing, declining and poor development. Specimens of two ring nematode were collected from the soil and identified as Mesocriconema sphaerocephalum (Taylor 1936) Loof 1989 and M. anastomoides (Maqbool & Shahina 1985) Loof & De Grisse 1989, based on the morphological and morphometrical analysis of females. Both nematodes have been previously found in Costa Rica. However, this is the first report of nematodes from the Criconematidae family associated to mulberry trees and it provides additional information on the distribution of this phytoparasite.